Psychopathology and psychotherapy : DSM-5 diagnosis, case conceptualization, and treatment - Sperry, Len. (New York : Routledge, 2015)
"Psychopathology & Psychotherapy: DSM-5 Diagnosis, Case Conceptualization, and Treatment, Third Edition differs from other psychopathology and abnormal psychology books. While other books focus on describing diagnostic conditions, this book focus on the critical link between psychopathology and psychotherapy. More specifically, it links diagnostic evaluation, case conceptualization, and treatment selection to psychotherapy practice. Research affirms that knowledge and awareness of these links is essential in planning and providing highly effective psychotherapy. This third edition incorporates detailed case conceptualizations and treatment considerations for the DSM-5 diagnoses most commonly seen in everyday clinical practice. Extensive case studies illustrate the diagnostic, case conceptualization, and treatment process in a way that makes it come alive. Written by practicing clinicians with expertise in specific disorders, this book will be an invaluable resource to both novice and experienced clinicians"--
1. Diagnosis, case conceptualization, culture, and treatment / Len Sperry -- 2. Adlerian case conceptualization / Len Sperry -- 3. Personality disorders / Len Sperry -- 4. Anxiety and obsessive-compulsive disorders / Jill Duba Sauerheber and James Robert Bitter -- 5. Depression and bipolar disorders / Paul R. Rasmussen and Dinko Aleksandrof -- 6. Trauma- and stressor-related disorders / Bret A. Moore and John F. Newbauer -- 7. Eating disorders / Mary Frances Schneider -- 8. Schizophrenia spectrum and other psychotic disorders / Len Sperry and Jon Sperry -- 9. Dissociative disorders / Jon Sperry and Len Sperry -- 10. Somatic symptoms and related disorders / Laurie Sackett-Maniacci and Michael P. Maniacci -- 11. Sleep-wake disorders / Jennifer N. Williamson and Daniel G. Williamson -- 12. Sexual disorders / Sharyl M. Trail -- 13. Neurodevelopmental and conduct disorders / Larry Maucieri -- 14. Substance use and addictive disorders / Mark T. Blagen -- 15. Neurocognitive disorders / Michael P. Maniacci and Len Sperry.
Keywords: Adler, Alfred, -- 1870-1937.; Diagnostic and statistical manual of mental disorders; Psychology, Pathological; Psychotherapy; Psychiatry -- Differential therapeutics